Manufacturing Industries’ Dynamics in Türkiye - İsmail Tuncer; Maya Moalla (Hitit Ekonomi ve Politika Dergisi)
The role of structural change in economic growth is well-documented for developed nations, yet studies on developing countries remain scarce. This study seeks to bridge this gap by exploring the influence of structural change on labor productivity in Turkey’s manufacturing sector at the 4-digit industry level from 2010 to 2015. Using microdata from the Turkish Statistical Institute's Annual Industry and Service Statistics, classified by NACE Rev.2, and covering 59214 firms, we apply the shift-share method. The results indicate that structural change exerted a drag on economic growth in this period, while labor productivity growth was largely driven by the within-growth effect